Probing the Impact of Temperature and Substrates on the Conformational Dynamics of the Neurotransmitter:Sodium symporter LeuT. Issue 2 (30th January 2022) - Calugareanu, Dionisie; Möller, Ingvar R.; Schmidt, Solveig G.; Loland, Claus J.; Rand, Kasper D.
Graphical abstract: Highlights: HDX-MS reveals the conformational impact of two substrates and temperature on LeuT. Binding of Ala versus Leu induces distinct differences in the dynamics of LeuT. Multiple regions in LeuT exhibited increased dynamics at elevated temperatures. EX1 kinetics is detected at elevated temperatures and in the presence of Ala/Leu. Both substrates and temperature modulate the slow dynamics (EX1) in LeuT. Abstract: The crucial function of neurotransmitter:sodium symporters (NSS) in facilitating the reuptake of neurotransmitters into neuronal cells makes them attractive drug targets for treating multiple mental diseases. Due to the challenges in working with eukaryotic NSS proteins, LeuT, a prokaryotic amino acid transporter, has served as a model protein for studying structure–function relationships of NSS family proteins. With hydrogen–deuterium exchange mass spectrometry (HDX-MS), slow unfolding/refolding kinetics were identified in multiple regions of LeuT, suggesting that substrate translocation involves cooperative fluctuations of helical stretches. Earlier work has solely been performed at non-native temperatures (25 °C) for LeuT, which is evolutionarily adapted to function at high temperatures (85 – 95 °C). To address the effect of temperature on LeuT dynamics, we have performed HDX-MS experiments at elevated temperatures (45 °C and 60 °C). At these elevated temperatures, multiple regions in LeuT exhibited increased dynamics compared to 25 °C. Interestingly, coordinated slow unfolding/refolding of key regions could still be observed, though considerably faster. We have further investigated the conformational impact of binding the efficiently transported substrate alanine (Ala) relative to the much slower transported substrate leucine (Leu). Comparing the HDX of the Ala-bound versus Leu-bound state of LeuT, we observe distinct differences that could explain the faster transport rate (kcat ) of Ala relative to Leu. Importantly, slow unfolding/refolding dynamics could still be observed in regions of Ala-bound LeuT . Overall, our work brings new insights into the conformational dynamics of LeuT and provides a better understanding of the transport mechanism of LeuT and possibly other transporters bearing the LeuT fold.